2010
DOI: 10.1111/j.1365-313x.2010.04359.x
|View full text |Cite
|
Sign up to set email alerts
|

LOST MERISTEMS genes regulate cell differentiation of central zone descendants in Arabidopsis shoot meristems

Abstract: SUMMARYMeristems of seed plants continuously produce new cells for incorporation into maturing tissues. A tightly controlled balance between cell proliferation in the center and cell differentiation at the periphery of the shoot meristem maintains its integrity. Here, we describe the role of three GRAS genes, named LOST MERISTEMS genes, in shoot apical meristem maintenance and axillary meristem formation. Under short photoperiods, the lom1 lom2 and lom1 lom2 lom3 mutants have arrested meristems characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
142
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(153 citation statements)
references
References 43 publications
(54 reference statements)
10
142
0
1
Order By: Relevance
“…Alternately, spatially localized coactivators in the CZ or corepressors in the RM could mediate the localized activation of CLV3. Biochemical studies have shown that the HAM proteins expressed in both the RM and the PZ interact with WUS (16,17). The genetic analysis revealed that HAM proteins require WUS function in regulating SAM maintenance (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternately, spatially localized coactivators in the CZ or corepressors in the RM could mediate the localized activation of CLV3. Biochemical studies have shown that the HAM proteins expressed in both the RM and the PZ interact with WUS (16,17). The genetic analysis revealed that HAM proteins require WUS function in regulating SAM maintenance (17).…”
Section: Discussionmentioning
confidence: 99%
“…It also is not known how CLV3 is transcribed in only a few cells of the CZ despite the presence of the WUS protein in a much broader spatial domain (6). WUS has been shown to interact with HAIRY MERISTEM (HAM) family proteins HAM1 and HAM2, which are expressed in the RM and lateral edges of the PZ (16,17). Perhaps HAM proteins may provide a spatial context for expression of CLV3 in the CZ.…”
mentioning
confidence: 99%
“…We performed a genome-wide analysis of sRNA phasing (Zhai et al, 2011) with the hen1 mutant sRNA libraries. Only the two loci AT2G45160 and AT3G60630, both of which regulate the development of shoot meristem (Schulze et al, 2010), produced phased siRNAs in hen1 mutants but not the wild type ( Figure 4A; see Supplemental Figure 5 online). These genes are both the predicted targets of miR170/171a (see Supplemental Figure 5 online).…”
Section: Modified Mirnas In Wild-type Plantsmentioning
confidence: 99%
“…WUS lacking the homodimerization sequences not only complemented wus-1 mutants but also caused meristem overproliferation, showing that homodimerization restricts meristem growth (17). An independent study has shown that WUS also interacts with HAIRYMERISTEM (HAM) proteins that are required for meristem maintenance (18,19). The HAM proteins haven been shown to bind the WUS sequence located between amino acids 203 and 236 (referred to as the HAM binding domain) (19).…”
Section: Significancementioning
confidence: 99%